Road Transport Process Management in the Courier Services Sector - Bilski, Tomasz (Towards Sustainable Transport in Logistics and International Trade, 2025)
This chapter examines logistics in the CEP sector and the role of road transport in the context of the growing importance of e-commerce. A quantitative approach was applied, based on the analysis of market data and surveys of customers using DHL services. The study shows that delivery time and price are the main factors influencing the choice of courier company, and that courier services are used regularly. Identified challenges include delays and low service quality. Practical implications concern the need to improve service quality and respond flexibly to changing market needs. The chapter also highlights the importance of door-to-door delivery and parcel collection points. From a social and environmental perspective, the authors discuss DHL's GoGreen and Mission 2050 initiatives aimed at reducing CO₂ emissions. The value of the study lies in its combination of market analysis with an evaluation of pro-environmental actions and consumer preferences in the CEP sector.